ANALYSIS AND DESIGN OF MSME PERFORMANCE MEASUREMENT SYSTEMS BASED ON GEOGRAPHIC INFORMATION SYSTEMS - Ismail Abdullah; Rienna Oktarina; Hendra Gunawan; Jessenia Wijaya; Arvin Wicaksono (Media Bina Ilmiah, 2023)
MSMEs are a pillar of the nation's economy (Ishak Effendi, 2005). With the contribution of MSMEs provided by GDP growing by 5% throughout 2019 and the contribution of MSMEs in 2020 reaching approximately 65% (BPS, 2019; 2020). The government needs to be supported by research on the performance of national MSMEs which are considered to require an integrated financial data processing information system with a spatial data information system throughout the Republic of Indonesia. Based on research conducted by the LLP-KUKM research section in 2021, 6 out of 10 people agreed and 3 out of 10 other people strongly agreed if the administrative process for MSMEs was carried out offline it would take time. Meanwhile, in the next survey, 5 out of 10 people agreed and 2 out of 10 people strongly agreed if they got an information system to measure the performance of MSMEs. This research was conducted with the aim of designing and building a platform using the DEA (Data Envelopment Analysis) method, measuring the performance and effectiveness of national MSMEs in each province and category throughout Indonesia and continued by measuring the performance of the geographic information system website using the webqual 4.0 method. The geographic information system website for measuring MSME performance in the MSME/user domain was built with the msme-research.com link, while the manager/administrator domain was built with the msme-research/dashboard link. It was concluded that the geographic information system was built and successfully sampled MSME data by spreading links/links in the MSME domain and obtained a sample of 292 MSME data, where the most provinces were obtained from West Java province, namely 95 MSMEs, the highest MSME performance by province was West Nusa Tenggara with the average performance value is 89.02%, the best performance by category is furniture with a performance value of 79.91%. Meanwhile, the measurement of the performance of the information system website which is filled out by 292 correspondents/MSMEs is with a value of 3.704 (which is in the interval between 3 and 4) which means good. Based on the results of usability testing, 75% of respondents stated that they quite understand the names of the fields used, and carry out the process of adding, deleting and editing data. It is recommended that the next development is to use only 2 financial data parameters with the consideration that if there are 14 parameters that must be submitted, MSMEs will feel bored with the filling process.